Gaya Belajar dan Implikasinya Terhadap Kemampuan Berfikir Kritis Mahasiswa - Ghofur, Abd; Nafisah, Durrotun; Eryadini, Ninies (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
This article examines concept of learning styles and the effect on students' critical thinking ability. According to United Nations (UN) critical thinking skills (critical thinking skills) is characteristic of the current era of globalization of society, namely the knowledge society (knowledge-based scoeity). But critical thinking is considered by most students is difficult, moreover, the lesson is still centered on the lecturer (Teacher Centered Learning) so that students are difficult to express ideas. So that students' critical thinking skills are still low. Learning style is considered to be a means to develop critical thinking abilities. It is based on the results of the study Nurbaeti, et al (2015) There is a positive relationship between learning style with critical thinking skills. Based on these descriptions, the necessary efforts to develop students' critical thinking skills by observing the learning style of each individual. Achievement of critical thinking skills of students affected by many factors, one of which is learning style. In addition to the use of appropriate teaching methods, learning styles also a motivating factor to achieve critical thinking skills. Because the student's learning style has a close connection with the achievement of the average value of critical thinking skills and cognitive abilities of learners